Update on Management Methods for Cycad Aulcaspis Scale - Greg S. Hodges; Forrest W. Howard; Eileen A. Buss (EDIS, 2003)
More than 20 species of scale insects occur on cycads in Florida, the most damaging of which is the cycad aulacaspis scale. This species was first found in Florida in 1996. Since this initial discovery in the Miami area, it has become widely distributed in Florida. Homeowners and nurserymen alike have been struggling with control of this pest. Populations of this scale readily reach high densities on their hosts, causing necrosis of fronds and eventually plant death. This document is ENY-680, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 2003.